2019
DOI: 10.1519/jsc.0000000000003129
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Internal vs. External Focus of Attention Instructions on Countermovement Jump Variables in NCAA Division I Student-Athletes

Abstract: Kershner, AL, Fry, AC, and Cabarkapa, D. Effect of internal vs. external focus of attention instructions on countermovement jump variables in NCAA Division I student-athletes. J Strength Cond Res XX(X): 000–000, 2019—The purpose of this study was compare the effect of internal and external focus of attention instructions on force-time characteristics of the countermovement jump (CMJ) in collegiate student-athletes. Forty-three resistance-trained men ( … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(47 citation statements)
references
References 19 publications
0
36
0
Order By: Relevance
“…On the other hand, when performing CMJ-S, athletes were instructed to start with arms positioned slightly in the front of the body with elbows flexed at a 90-degree angle and finish with the arms extended above the head. All athletes were verbally encouraged to give maximal effort and focus on pushing away from the ground as explosively as possible [ 15 ]. The best score obtained from three total attempts for each jump test was recorded and used for performance analysis purposes.…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, when performing CMJ-S, athletes were instructed to start with arms positioned slightly in the front of the body with elbows flexed at a 90-degree angle and finish with the arms extended above the head. All athletes were verbally encouraged to give maximal effort and focus on pushing away from the ground as explosively as possible [ 15 ]. The best score obtained from three total attempts for each jump test was recorded and used for performance analysis purposes.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, the external focus provoked rapid opening of ankle, knee, and hip angles together, leading to an overall improved task performance [ 34 ]. Interestingly, peak force (ground reaction forces measured by a force plate) and peak power in a jump-and-reach task did not change, albeit higher jumping performance in EF condition for trained athletes [ 35 ]. This result might be due to an optimized co-ordination of all body parts or due to better harmonized timing of movement elements to realize higher jumps.…”
Section: Discussionmentioning
confidence: 99%
“…Such findings have been found across a variety of different motor tasks, regardless of age, (dis)ability, and level of expertise ( Wulf, 2013 ; Chua et al, 2021 ). In particular, an EF has been found to be more effective than an IF for motor tasks where velocity plays a crucial role for optimizing outcome performance ( An et al, 2013 ; Lohse et al, 2014 ; Halperin et al, 2017 ; Kershner et al, 2019 ). For example, An et al (2013) investigated the golf swing and reported an increased X-factor stretch during the backswing, carry distance, and angular velocities of the pelvis, shoulder, and wrist when adopting an EF (e.g., push against the left side of the ground as you hit the ball) relative to an IF (e.g., transfer your weight to your left foot as you hit the ball) or control (e.g., no-focus instruction) group.…”
Section: Introductionmentioning
confidence: 99%
“…Investigating a punching task, Halperin et al (2017) found that “focus on punching the pad as fast and as forcefully as possibly” (EF) compared to “focus on moving your arm as fast and as forcefully as possibly” (IF) increased velocity and punch impact. In a study on a countermovement jump, Kershner et al (2019) reported an increased mean velocity and squat jump height when participants were asked to “concentrate on pushing away from the ground as explosively as possible” (i.e., EF) versus when they were required to “concentrate on extending your knees and hips as explosively as possible” (i.e., IF). As such, evidence suggests that an EF relative to an IF promotes increased angular velocities in motor tasks where velocity is a critical element for successful performance.…”
Section: Introductionmentioning
confidence: 99%